Students Critical Thinking Development in National Sciences and Mathematics Competition in Indonesia: A Descriptive Study (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aimed to describe the development of students’ critical thinking through their participation in the National Sciences and Mathematic Competition in Indonesia, known as Olimpiade Nasional Matematika dan IPA (ONMIPA). Furthermore, this study investigated the response of the participants towards the administration of ONMIPA in various aspects and also examined support given by the institution to their students related to ONMIPA administration. A qualitative approach implemented to answer the research questions. The instruments used to collect the data were observations list, questionnaire, and interview. The respondents of this study were 54 ONMIPA participants and ten ONMIPA 2019. The study revealed that The National Mathematics and Natural Sciences Olympiad or ONMIPA had excellent potential to develop students’ critical thinking skills. The data showed that participants’ responses to the administration of ONMIPA were very positive. Besides, the result revealed that Higher education institutions provided support to participants and the administration of ONMIPA. The support was generally excellent and provided in various forms.